Cyberscape: Designing an Escape Room Game with a Computer Network Security Theme to Encourage Understanding of Network Security Concepts Interactively - Rahman, Rakhmadi; Hakim, Lukman; Pusung, Noel Ivander (Educational Insights, 2024)
Network security is a crucial aspect in the IT world, especially the increasing activity of crecker in carrying out attacks without responsibility. cyberscape is an educational game that will be designed to provide a fundamental understanding of the importance of overcoming crecker attacks on the network. The method used in designing this game is the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) approach. In the analysis stage, needs collection and determination of learning objectives are carried out. The design stage includes storyboarding and game design. Characters and other visual elements are designed using pixil art techniques to provide a unique and attractive appearance. The development stage involves creating game content, initial testing, and code implementation using Unity Game Engine integrated with C# programming language. The implementation stage includes the deployment of the game to users. The results showed that "Cyberscape" was effective in improving players' understanding of basic network security concepts. Users reported a significant increase in their knowledge of how to identify and overcome cracker attacks after playing the game. Qualitative and quantitative evaluations showed a high level of satisfaction among users, as well as an increased awareness of the importance of network security. With this approach, it is hoped that "Cyberscape" can be an effective tool in network security education and help reduce vulnerability to cracker attacks.